Productivity and Foreign Direct Investment in The Services Sector: An Econometric Analysis - Lopes Coimbra, Juliano César; Gandra de Carvalho, Ana Catarina; Polloni Silva, Eduardo; Fernando Moralles, Herick (Revista Gestão da Produção Operações e Sistemas, 2023)
The Foreign Direct Investments (FDIs) in the service sector have become increasingly important for emerging economies, due to the spillover effects they can generate and that drive regional economic development. In this study, we investigate the regional effects of FDI in services on the productivity of receiving municipalities. To do so, we employ econometric models to measure the impact of FDI in services at the municipal level in São Paulo, the most intensive FDI state in Brazil, between 2010 and 2016. Our results indicate a positive relationship between FDI in services and municipal productivity, providing valuable insights for the development of FDI attraction policies. These findings have important implications for the service sector and can serve as a reference for future studies related to the topic